Effect Of Caffeine and Adrenaline on Memory and Anxiety in Male Wistar Rats (Nigerian Journal of Physiological Sciences, 2022)
The present study was designed to investigate the effects of caffeine and adrenaline administration on memory and anxiety in male rats. Rats weighing about 140-200g were used for the study. They were divided into three groups (4 animals per group). Study groups 1; a,b,c,d were healthy rats administered normal saline, 5,10 and 15mg/kg bw caffeine intraperitoneally (i.p.), respectively for 6 weeks. Study groups 2; a,b,c,d administered normal saline, 0.1, 0.2 and 0.31mg/kg bw adrenaline (i.p.), respectively for 6 weeks. Study groups 3; a,b,c,d administered normal saline, 5mg/kg caffeine (i.p.) + 0.1mg/kg adrenaline (i.p.), 10mg/kg Caffeine (i.p.) + 0.2mg/kg Adrenaline (i.p.) and 15mg/kg Caffeine (i.p.) + 0.3mg/kg Adrenaline (i.p.) respectively for 6 weeks. The result showed no significant difference in spatial memory across all animals in study groups 1: b,c,d when compared to control (a). Study groups 2: (b, c) showed increase in spatial memory when compared to control (a). 2(d) showed a significant (p